A process-based approach to exploring the information behavior of informal caregivers of people living with dementia. (January 2021) - Rutkowski, Rachel A.; Ponnala, Siddarth; Younan, Laura; Weiler, Dustin T.; Bykovskyi, Andrea Gilmore; Werner, Nicole E.
Highlights: Informal caregivers of people with dementia have persistent unmet information needs. We developed a conceptual framework of dementia caregiver information behavior. Our framework uses a process-level, sociotechnical-systems-based perspective. Our framework guides information product and process design for dementia caregivers. Abstract: Introduction and purpose: Informal caregivers of persons living with dementia have significant unmet information needs that, if met, would better equip them to provide effective care. Despite the existence of health information technologies, websites, resources, and organizations dedicated to dementia caregiving, caregivers continue to report unmet information needs. Caregivers' continued unmet information needs suggest a misalignment between information products, and caregivers' information behavior—how caregivers generate, acquire, manage, use, communicate, and seek information. Researchers have developed conceptual models for understanding caregivers' information behavior, but these models are limited in that they are task-oriented, and they assume that caregivers' information needs will be met if they engage in information behavior. To address these limitations, the present study sought to explore caregivers' information behavior as a sociotechnical-systems-based process. Methods: We conduced semi-structured interviews with 30 self-identified caregivers to explore their daily experience of caregiving activities, including their information behavior. We applied a process-based conceptual framework that takes into account inputs, processes, outputs, and feedback mechanisms within a sociotechnical system to guide analysis. The process of interest was caregivers' information behavior as modeled by the information-seeking and communication model (ISCM). We conducted a deductive content analysis guided by the components of the ISCM. We then used team-based affinity diagramming to collapse and categorize the ISCM components into inputs, processes, outputs, and feedback. Results: We developed a conceptual model to depict caregivers' information behavior as a sociotechnical-systems-based process of inputs, processes, and outputs that feedback into the system. The conceptual model consisted of three inputs (i.e., information users, information providers, and information products), three information seeking and communication processes (i.e., information access, information interaction, and information assessment and processing), two outputs (i.e., utility and credibility), and feedback. Discussion and conclusion: Building on and addressing the gaps in previous information behavior models, our conceptual framework advances the previous task-level understandings of caregivers' information behavior into a comprehensive feedback-driven, process-level perspective consisting of context-based inputs, information seeking and communication processes, outputs, and feedback. A sociotechnical-systems-based understanding of caregivers' information behavior allows for misalignments between information providers and products, and caregivers' information behavior not only to be illuminated, but systematically addressed.